Water temperature affects osmoregulatory responses in gilthead sea bream (Sparus aurata L.). (February 2020) - Vargas-Chacoff, Luis; Arjona, Francisco J.; Ruiz-Jarabo, Ignacio; García-Lopez, Angel; Flik, Gert; Mancera, Juan M.
Abstract: Sea bream ( Sparus aurata Linneaus) was acclimated to three salinity concentrations, viz . 5 (LSW), 38 (SW) and 55psμ (HSW) and three water temperatures regimes (12, 19 and 26 °C) for five weeks. Osmoregulatory capacity parameters (plasma osmolality, sodium, chloride, cortisol, and branchial and renal Na +, K + -ATPase activities) were also assessed. Salinity and temperature affected all of the parameters tested. Our results indicate that environmental temperature modulates capacity in sea bream, independent of environmental salinity, and set points of plasma osmolality and ion concentrations depend on both ambient salinity and temperature. Acclimation to extreme salinity resulted in stress, indicated by elevated basal plasma cortisol levels. Response to salinity was affected by ambient temperature. A comparison between branchial and renal Na +, K + -ATPase activities appears instrumental in explaining salinity and temperature responses. Sea bream regulate branchial enzyme copy numbers (Vmax ) in hyperosmotic media (SW and HSW) to deal with ambient temperature effects on activity; combinations of high temperatures and salinity may exceed the adaptive capacity of sea bream. Salinity compromises the branchial enzyme capacity (compared to basal activity at a set salinity) when temperature is elevated and the scope for temperature adaptation becomes smaller at increasing salinity. Renal Na +, K + -ATPase capacity appears fixed and activity appears to be determined by temperature. Highlights: The temperature and salinity are modifying the osmotic responses in fish. The plasma osmolality is modulates by temperature more than salinity. The Na + and Cl − concentration depend on both ambient salinity and temperature. The response NKA activity to different combinations of salinity and temperature are related to the assay conditions used.